Work-values of students preparing for different occupations: A contribution to validation of the WIS Values Scale - Šverko, Branimir (Array, 1987)
A new, internationally developed Values Scale measuring 20 values was administered to six university-student groups pursuing curricula for different occupations (engineering, business, architecture, psychology, medicine, and social work). Significant differences in their work-values profiles have been found and interpreted. The obtained differences were generally conceivable, and in accordance with the predictions stated before. It was concluded that the results contributed important evidence for the validity of the new values inventory.